2021
DOI: 10.1080/19420862.2021.1887612
|View full text |Cite
|
Sign up to set email alerts
|

Identification of critical chemical modifications by size exclusion chromatography of stressed antibody-target complexes with competitive binding

Abstract: Chemical modifications (attributes) in the binding regions of stressed therapeutic proteins may affect binding to target and efficacy of therapeutic proteins. The method presented here describes the criticality assessment of therapeutic antibody modifications by size-exclusion chromatography (SEC) of competitive binding between a stressed antibody and its target, human epidermal growth factor receptor-2 (HER2), followed by SEC fractionation and peptide mapping characterization of bound and unbound antibodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Moreover, the acidic peaks of thermal stressed sample exhibited an increase in masses in comparison to the control mAb A, likely due to the deamidation of asparagine. Other researchers have observed that the elevated temperature results in deamidation of the asparagine, which increased the acidic species in the sample, by enhancing deamidation, N-terminal glutamine cyclization, and oxidation-based modifications . In the present study, deamidated acidic species were observed according to their deconvoluted masses.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Moreover, the acidic peaks of thermal stressed sample exhibited an increase in masses in comparison to the control mAb A, likely due to the deamidation of asparagine. Other researchers have observed that the elevated temperature results in deamidation of the asparagine, which increased the acidic species in the sample, by enhancing deamidation, N-terminal glutamine cyclization, and oxidation-based modifications . In the present study, deamidated acidic species were observed according to their deconvoluted masses.…”
Section: Resultssupporting
confidence: 56%
“…Other researchers have observed that the elevated temperature results in deamidation of the asparagine, which increased the acidic species in the sample, 27 by enhancing deamidation, N-terminal glutamine cyclization, and oxidation-based modifications. 24 In the present study, deamidated acidic species were observed according to their deconvoluted masses. Additionally, two basic peaks were observed in the thermal stressed sample, peak B1 with a ∼16 Da and peak B2 with a ∼30 Da additional mass, likely due to 1X and 2X oxidation of the stressed sample (Table 3).…”
Section: Table 1 Operating Conditions Used For Performing 2d-sec-ms-w...mentioning
confidence: 71%
See 2 more Smart Citations
“…Subsequent bottom-up MS analysis of these SEC fractions could identify attributes that were enriched in the unbound fraction due to impaired antigen binding. 23 Shi et al 24 further incorporated a competitive binding step to this workflow and showed improved method sensitivity in identifying attributes with less significant effects on target binding. This SEC fractionation and bottom-up MS-based approach significantly improved the method throughput in pCQA evaluation.…”
Section: Introductionmentioning
confidence: 99%